Which of the following functions are homogeneous?
A) \[x\sin y + y\sin x\]
B) \[x{e^{y/x}} + y{e^{x/y}}\]
C) \[{x^2} - xy\]
D) \[\arcsin (xy)\]
Answer
Verified
442.2k+ views
Hint:
Here, we have to find the functions which are homogeneous. We will find the functions which are homogeneous by using the condition of homogeneity. A homogeneous function is one with multiplicative scaling behavior i.e., if all its arguments are multiplied by a factor, then its value is multiplied by some power of this factor.
Formula Used:
A homogeneous function is a function which satisfies the condition,
\[f(tx,ty) = {t^n}f(x,y)\] for some \[n > 0\]
Complete step by step solution:
We are given functions, to check whether it is a homogeneous function.
A homogeneous function is a function which satisfies the condition,
\[f(tx,ty) = {t^n}f(x,y)\] for some \[n > 0\].
A) \[f\left( {x,y} \right) = x\sin y + y\sin x\]
Now, by using the homogeneity condition, we will get
\[ \Rightarrow f\left( {tx,ty} \right) = tx\sin \left( {ty} \right) + ty\sin \left( {tx} \right)\]
Factoring out common terms, we get
\[ \Rightarrow f\left( {tx,ty} \right) = = t\left( {x\sin ty + y\sin tx} \right)\]
But \[x\sin ty + y\sin tx \ne f\left( {x,y} \right)\]
Hence it is not a homogeneous function.
B) \[f\left( {x,y} \right) = x{e^{y/x}} + y{e^{x/y}}\]
Now, by using the homogeneity condition, we will get
\[ \Rightarrow f\left( {tx,ty} \right) = tx{e^{ty/tx}} + ty{e^{tx/ty}}\]
Factoring out common terms, we get
\[ \Rightarrow f\left( {tx,ty} \right) = t\left( {x{e^{y/x}} + y{e^{x/y}}} \right)\]
\[ \Rightarrow f\left( {tx,ty} \right) = tf\left( {x,y} \right)\]
Hence it is a homogeneous function.
C) \[f\left( {x,y} \right) = {x^2} - xy\]
Now, by using the homogeneity condition, we will get
\[ \Rightarrow f\left( {tx,ty} \right) = {(tx)^2} - txty\]
\[ \Rightarrow f\left( {tx,ty} \right) = {t^2}{x^2} - {t^2}xy\]
Factoring out common terms, we get
\[ \Rightarrow f\left( {tx,ty} \right) = {t^2}({x^2} - xy)\]
\[ \Rightarrow f\left( {tx,ty} \right) = {t^2}f\left( {x,y} \right)\]
Hence it is a homogeneous function.
D) We know that \[\arcsin (xy) = {\sin ^{ - 1}}(xy)\]
\[ \Rightarrow f\left( {x,y} \right) = {\sin ^{ - 1}}\left( {xy} \right)\]
Now, by using the homogeneity condition, we will get
\[ \Rightarrow f\left( {tx,ty} \right) = {\sin ^{ - 1}}\left( {txty} \right)\]
Factoring out common terms, we get
\[ \Rightarrow f\left( {tx,ty} \right) = {\sin ^{ - 1}}\left( {{t^2}(xy)} \right)\]
But \[{\sin ^{ - 1}}\left( {{t^2}(xy)} \right) \ne f\left( {x,y} \right)\]
Hence it is not a homogeneous equation.
Therefore, the functions \[x{e^{y/x}} + y{e^{x/y}}\] and \[{x^2} - xy\] are homogeneous functions.
Note:
We should be very conscious in finding whether the given functions are homogeneous or not. We should replace the variable \[x\] by multiplying the variable with any constant \[tx\]. The zero function is homogeneous of any degree. The sum of homogeneous functions of the same homogeneous degree is also homogeneous of the same degree, unless it is identically the zero function. The product of homogeneous functions of degrees \[{d_1}\] and \[{d_2}\] is homogeneous of degree \[{d_1} + {d_2}\] . The reciprocal of a homogeneous function of degree d is homogeneous of degree −d. The k th power of a homogeneous function of degree \[d\] is homogeneous of degree \[kd\] . These are the rules of homogeneous function.
Here, we have to find the functions which are homogeneous. We will find the functions which are homogeneous by using the condition of homogeneity. A homogeneous function is one with multiplicative scaling behavior i.e., if all its arguments are multiplied by a factor, then its value is multiplied by some power of this factor.
Formula Used:
A homogeneous function is a function which satisfies the condition,
\[f(tx,ty) = {t^n}f(x,y)\] for some \[n > 0\]
Complete step by step solution:
We are given functions, to check whether it is a homogeneous function.
A homogeneous function is a function which satisfies the condition,
\[f(tx,ty) = {t^n}f(x,y)\] for some \[n > 0\].
A) \[f\left( {x,y} \right) = x\sin y + y\sin x\]
Now, by using the homogeneity condition, we will get
\[ \Rightarrow f\left( {tx,ty} \right) = tx\sin \left( {ty} \right) + ty\sin \left( {tx} \right)\]
Factoring out common terms, we get
\[ \Rightarrow f\left( {tx,ty} \right) = = t\left( {x\sin ty + y\sin tx} \right)\]
But \[x\sin ty + y\sin tx \ne f\left( {x,y} \right)\]
Hence it is not a homogeneous function.
B) \[f\left( {x,y} \right) = x{e^{y/x}} + y{e^{x/y}}\]
Now, by using the homogeneity condition, we will get
\[ \Rightarrow f\left( {tx,ty} \right) = tx{e^{ty/tx}} + ty{e^{tx/ty}}\]
Factoring out common terms, we get
\[ \Rightarrow f\left( {tx,ty} \right) = t\left( {x{e^{y/x}} + y{e^{x/y}}} \right)\]
\[ \Rightarrow f\left( {tx,ty} \right) = tf\left( {x,y} \right)\]
Hence it is a homogeneous function.
C) \[f\left( {x,y} \right) = {x^2} - xy\]
Now, by using the homogeneity condition, we will get
\[ \Rightarrow f\left( {tx,ty} \right) = {(tx)^2} - txty\]
\[ \Rightarrow f\left( {tx,ty} \right) = {t^2}{x^2} - {t^2}xy\]
Factoring out common terms, we get
\[ \Rightarrow f\left( {tx,ty} \right) = {t^2}({x^2} - xy)\]
\[ \Rightarrow f\left( {tx,ty} \right) = {t^2}f\left( {x,y} \right)\]
Hence it is a homogeneous function.
D) We know that \[\arcsin (xy) = {\sin ^{ - 1}}(xy)\]
\[ \Rightarrow f\left( {x,y} \right) = {\sin ^{ - 1}}\left( {xy} \right)\]
Now, by using the homogeneity condition, we will get
\[ \Rightarrow f\left( {tx,ty} \right) = {\sin ^{ - 1}}\left( {txty} \right)\]
Factoring out common terms, we get
\[ \Rightarrow f\left( {tx,ty} \right) = {\sin ^{ - 1}}\left( {{t^2}(xy)} \right)\]
But \[{\sin ^{ - 1}}\left( {{t^2}(xy)} \right) \ne f\left( {x,y} \right)\]
Hence it is not a homogeneous equation.
Therefore, the functions \[x{e^{y/x}} + y{e^{x/y}}\] and \[{x^2} - xy\] are homogeneous functions.
Note:
We should be very conscious in finding whether the given functions are homogeneous or not. We should replace the variable \[x\] by multiplying the variable with any constant \[tx\]. The zero function is homogeneous of any degree. The sum of homogeneous functions of the same homogeneous degree is also homogeneous of the same degree, unless it is identically the zero function. The product of homogeneous functions of degrees \[{d_1}\] and \[{d_2}\] is homogeneous of degree \[{d_1} + {d_2}\] . The reciprocal of a homogeneous function of degree d is homogeneous of degree −d. The k th power of a homogeneous function of degree \[d\] is homogeneous of degree \[kd\] . These are the rules of homogeneous function.
Recently Updated Pages
Master Class 12 Economics: Engaging Questions & Answers for Success
Master Class 12 Maths: Engaging Questions & Answers for Success
Master Class 12 Biology: Engaging Questions & Answers for Success
Master Class 12 Physics: Engaging Questions & Answers for Success
Master Class 12 Business Studies: Engaging Questions & Answers for Success
Master Class 12 English: Engaging Questions & Answers for Success
Trending doubts
Which are the Top 10 Largest Countries of the World?
Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE
Draw a labelled sketch of the human eye class 12 physics CBSE
What is the Full Form of PVC, PET, HDPE, LDPE, PP and PS ?
What is a transformer Explain the principle construction class 12 physics CBSE
What are the major means of transport Explain each class 12 social science CBSE